Adultère, indices médicaux et recul de la torture à Genève (XVIIe siècle) - Sara Beam (Genre & Histoire)
This article investigates how the practice of judicial torture was shaped by attitudes to sin, to gender, and to the testimony of medical experts in seventeenth-century Geneva. In 1645, Nicolarde Boeuf was found to have syphilis and was charged with adultery, a crime that, when proven, sometimes resulted in a sentence of execution in Geneva.  When she denied the charges, she was tortured repeatedly, found guilty, and ultimately hanged. Whereas other scholars have argued that growing reliance on medical experts reduced the need for torture in criminal trials, this analysis reveals that early modern assumptions about the seriousness of female marital infidelity and about the importance of females as vectors of sexually transmitted diseases led the judges to torture Nicolarde until she produced a confession of guilt.  The practice of torture declined in Geneva not because of increased reliance on medical experts but because Genevan judges eventually decided that sexual and moral crimes such as adultery did not warrant the death penalty.